Competitions for the design of Orthodox churches in Niš 1998-2021 - Stanimirović, Mirko (Arhitektura i urbanizam, 2022)
This paper presents the competitions for developing urban-architectural solutions for Orthodox churches in Niš which took place from 1998 to 2021. In the past two years, student competitions for churches in Niš have taken place under the theme of “Sacred Architecture” at the Faculty of Civil Engineering and Architecture, University of Niš, in cooperation with the Orthodox Diocese of Niš. In addition to documenting the award-winning works, the paper analyzes the results of the competitions, with the aim of improving competition practice. The review of the competition entries is also related to the possibility of introducing sacral architecture into architectural educational, with the aim of improving the architectural design of Serbian Orthodox churches and documenting the competitions in Niš in order to development ideas for Serbian Orthodox churches. Based on the entries presented and analysis of the award-winning solutions, the importance of this phenomenon is highlighted.